The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1590/1806-9282.20220982
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fat graft and platelet-rich fibrin combination after epineurectomy in rats

Abstract: OBJECTIVE: One of the most important factors that adversely affects the outcome of peripheral nerve surgery is the formation of epineural and extraneural scar tissue after surgery. Many surgical methods and pharmacological and chemical agents have been used to prevent the formation of epineural scar tissue, but satisfactory results have not been achieved in clinical applications. The purpose of this study was to investigate the combined effect of fat graft and platelet-rich fibrin on the formation of epineural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The scientific literature indicates the efficiency of immunofluorescence methods for analyzing the regeneration of Schwann cells and peripheral remyelination [61,62]. In agreement, Kastamoni et al (2023) [32] found that the expression of EphA4 was associated with a negative effect on the axonal repair of the sciatic nerve, consistent with previous studies [63][64][65].…”
Section: Histological Analysissupporting
confidence: 82%
“…The scientific literature indicates the efficiency of immunofluorescence methods for analyzing the regeneration of Schwann cells and peripheral remyelination [61,62]. In agreement, Kastamoni et al (2023) [32] found that the expression of EphA4 was associated with a negative effect on the axonal repair of the sciatic nerve, consistent with previous studies [63][64][65].…”
Section: Histological Analysissupporting
confidence: 82%